Navigating Differences : Integration in Singapore - Chong, Terence (Book collections on Project MUSE., 2020)
Ethnic and religious differences, a widening socio-economic divide, tension between foreigners and locals. These are some of the contemporary challenges to integration in Singapore. How we navigate them will determine the type of society we become. This book gathers the best social scientists in Singapore to examine issues of ethnicity, religion, class, and culture in order to understand the many different fault lines that run across the multicultural city-state. These essays are written in an engaging manner and are designed to present the authors' expertise to a wider audience.